Public involvement in health research: what does ‘good’ look like in practice? - Kristin Liabo; Kate Boddy; Silvia Bortoli; Jenny Irvine; Heather Boult; Mary Fredlund; Neil Joseph; Gretchen Bjornstad; Christopher Morris (Research Involvement and Engagement, 2020)
Plain English summary Background Patient and public involvement means researchers working with members of the public, patients or carers to jointly plan and carry out research. Aim This article is written by members of three involvement groups, and the university employees that they work with. We wanted to jointly reflect on what enables our collaborative work, and what the challenges are for everyone involved. What we did and how we did it We wanted to establish what the literature defines as ‘good’ public involvement and compare this with processes and practices in our involvement groups. We therefore carried out a literature review and each group met separately to discuss what characterises good involvement, and what the challenges are. From these discussions we developed a set of descriptions about each group. We compared the literature review findings with what came out of the discussions within the involvement groups. Findings Some of the involvement principles from the literature were similar to the priorities of the involvement groups. In addition, the groups identified characteristics of ‘good’ involvement practice that were not reported in the literature: passion and enthusiasm, informal and welcoming meeting spaces, and opportunities to share lived experiences. In this article we present examples of how principles for good involvement are practiced in these groups, and difficulties we have experienced. Abstract Background Patient and public involvement is important for producing relevant and accessible health research. Evidence of impact from involvement is growing, but there is also a need for research on how to create conditions for meaningful collaborations between researchers and public advisers. Objective We report on a co-produced self-reflective evaluation of involvement practices in three UK research programmes. Methods A structured review identified research-based principles for ‘good’ public involvement in research. In parallel, members of three involvement groups co-developed statements on how the groups work, and enablers and challenges to collaborative research. The author team analysed these statements using the findings from the review. Results We identified 11 international articles reporting research-based principles for involvement published between 2013 and 2017. We identified five ‘values’ and seven ‘practice principles’ for ‘good’ involvement. There was convergence between these principles and the priorities of the involvement groups. But the groups also identified additional good involvement practice that were not reported by the literature: passion, enthusiasm, informal and welcoming meeting spaces, and opportunities to share lived experiences. We present examples of how principles for good involvement are practiced in these groups, and highlight principles that have been challenging to implement. Conclusions Ongoing appraisal of public involvement is crucial. We present a process for self-evaluation, illuminate what ‘good’ means to researchers and public advisers involved in research, and identify areas for improvement. We conclude that provision of resources that enable support to public advisers in turn enable universities and research teams to implement other principles of good involvement.